Perubahan Perilaku Petani dalam Usahatani Tanaman Kopi dengan Implementasi Sistem Pertanian Berkelanjutan - Farid Azel; Novfirman; Fastabiqul Khairad; Dara Latifa; Muhammad Syakib Sidqi; Ispinimiartriani; Sri Nofianti; Elviati (Fakultas Pertanian Universitas Ratu Samban, 2024)
Sustainable agricultural technology is essential as a solution to the need for improving the quantity and quality of agricultural production. Reimplementing sustainable agricultural technology requires time, financial resources, energy, and efforts from all stakeholders. The adoption of sustainable agricultural technology is crucial to restoring and preserving the quality of agricultural commodities. The adoption process, which is expected to be carried out by farmers, must be accompanied by agricultural extension workers as representatives of the government. It is necessary to gather information on the extent to which the adoption process of this technology has been implemented. The Focus Group Discussion (FGD) method, as a qualitative social research approach, can serve as a tool for evaluating programs and gaining deeper insights into the collective behavioral patterns of farmers participating in these programs. The results of the FGD-based research revealed that the adoption rate among farmers has reached nearly 70%, with a success rate of 71%. The study also found that the success of farmers was significantly influenced by the contributions of related government agencies that provided sustainable agricultural technology, as well as by farmers’ own independent innovations. Moreover, the greatest success factor was the assistance provided by local agricultural extension workers